Implementasi RAD dalam Rancang Bangun Sistem Penerimaan Murid Baru (SPMB) Di SMK Muhammadiyah Gambiran - Heru Tri Ahmanto; Sugeng Hendra Wijaya (Jurnal Informatika dan Komputer, 2026)
This study discusses the design and development of a webbased New Student Admission System (SPMB) at SMK Muhammadiyah 9 Gambiran using the Research and Development method, which includes the stages of requirements analysis, system design, database creation, and implementation.  In its development, the information system was built using the PHP programming language and supported by frontend technologies such as HTML and CSS, to produce a dynamic, flexible, and easily scalable web application for the new student admission system (SPMB). The ultimate goal of this research is to create a new student admissions information system (SPMB) that offers a more intuitive interface, faster access to key features such as news, announcements, form filling, and docume~nt uploads, and responsive display support across various devices.